Transcendental Philosophy and Intersubjectivity: Mutual Recognition as a Condition for the Possibility of Self‐Consciousness in Sections 1–3 of Fichte's Foundations of Natural Right. (14th February 2016) - McNulty, Jacob
Abstract: In the opening sections of his Foundations of Natural Right, Fichte argues that mutual recognition is a condition for the possibility of self‐consciousness. However, the argument turns on the apparently unconvincing claim that, in the context of transcendental philosophy, conceptions of the subject as an isolated individual give rise to a vicious circle the resolution of which requires the introduction of a second rational being to 'summon' the first. In this essay, my aim is to present a revised account of the opening arguments on which they are more convincing. In particular, I argue that the problem of a circle is genuine and may be seen to result from a relation of mutual dependence between agency and cognition which ensures that for an exercise of either capacity to take place, an exercise of the other would have already had to have taken place with the result that neither can occur. Moreover, the solution is successful. The summons (the claim of the other) prevents us from being driven around the circle once more because it is a 'synthesis' that reconciles the constraint to which I am subject as a cognizer of independently given objects and my freedom as a self‐determining subject.